Impact of deoxygenation and hydrological changes on the Black Sea nitrogen cycle during the Last Deglaciation and Holocene - A. Cutmore; N. Bale; R. Hennekam; B. Yang; D. Rush; G.-J. Reichart; G.-J. Reichart; E. C. Hopmans; S. Schouten; S. Schouten (Climate of the Past)
The marine nitrogen (N) cycle profoundly impacts global ocean productivity. Amid rising deoxygenation in marine environments due to anthropogenic pressures, understanding the impact of this on the marine N cycle is vital. The Black Sea's evolution from an oxygenated lacustrine basin to an anoxic marine environment over the Last Deglaciation and Holocene offers insight into these dynamics. Here, we generated records of the organic biomarkers heterocyte glycolipids (HGs), crenarchaeol, and bacteriohopanetetrol, associated with various water column microbial N-cycle processes, which indicate a profound change in Black Sea N-cycle dynamics at ∼7.2 ka when waters became severely deoxygenated. This transition substantially reduced Thaumarchaeota-driven nitrification and enhanced loss of bioavailable nitrogen through anaerobic ammonium oxidation (anammox). In contrast, other climatic changes over the Last Deglaciation and Holocene, such as freshwater input, water-level variations, and temperature changes, did not impact these processes. Cyanobacterial nitrogen fixation in surface waters proved more responsive to changes in salinity, which affected species composition, and associated water column stratification, which reduced the vertical transport of nutrients. Our results indicate that future deoxygenation in certain marine environments may enhance bioavailable nitrogen loss by anammox and reduce nitrification by Thaumarchaeota, while enhanced stratification may increase cyanobacterial nitrogen fixation in the surface waters.